Impact of containment type on Covid-19 propagation in Morocco using the SIR model. (Bangladesh Journal of Medical Science, 2020)
Objective and mehtods: Our objective is to determine the containment effect on the spread of Covid 19 in Morocco. The methodology is based on an epidemiological study whose objective is to take stock of the current situation and to estimate the future spread of Covid-19 over time in Morocco. Several conditions were considered using the SIR epidemiological model for a better reliability of the results. During the study period from the appearance of the first case until 19 June 2020, Morocco reported 9074 cases of infections, 213 deaths with a lethality of 2.35% and a mortality of 6.04 per million inhabitants.Results and Conclusion: The results of the SIR model show a sudden increase in infections. The peak would be 4.4 million inhabitants or 12% of the total population under confined conditions. Selon ces résultats,Containment is one of the most effective methods of reducing the risk of infection.Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 58-S 65